Analisis Pengaruh Kualitas Pelayanan Program Bpjs Terhadap Kepuasan Pasien Dimediasi Oleh Kinerja Medis - Anvika Anvika (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2019)
The quality of hospital services is an important element in health care services Patient satisfaction is considered as one of the most important dimensions of quality and is one of the main indicators of the standard of a health facility which is the result of influence on health services delivered by the hospital and this is what makes measuring patient satisfaction as an important component. Objective is to analyze the effect on service quality of BPJS program toward patient satisfaction mediated by medical performance in Jambi. This research was quantitative with cross sectional study design. Whole patients using BPJS service in RSUD Raden Mattaher Jambi were 12,000 people. The sample of this study was 108 people with sampling technique of purposive sampling. Structural Equation Modeling (SEM) was used to analysis. Results are The quality of BPJS program services has a positive and significant effect on patient satisfaction. The quality of BPJS program services has a positive and significant effect on medical performance. The medical performance has a positive and significant effect on patient satisfaction. BPJS program service quality has a positive and significant effect on patient satisfaction mediated by medical performance in Jambi